2020
DOI: 10.1371/journal.pone.0244198
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic analysis of lettuce (Lactuca sativa L.) reveals starch and sucrose metabolism functions during bolting induced by high temperature

Abstract: High temperatures induce early bolting in lettuce (Lactuca sativa L.), which decreases both quality and production. However, knowledge of the molecular mechanism underlying high temperature promotes premature bolting is lacking. In this study, we compared lettuce during the bolting period induced by high temperatures (33/25 °C, day/night) to which raised under controlled temperatures (20/13 °C, day/night) using iTRAQ-based phosphoproteomic analysis. A total of 3,814 phosphorylation sites located on 1,766 phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Studies on the effect of WD on starch are scanty: Sun-Ok and Dong-Hoon [43] found that WD concentrations of up to 0.5% decreased the leaf starch content of the orchid Neofinetia falcata but increased its root content. We have not assayed the root parts of the plant, but the starch content of our control lettuce leaves was consistent with that reported in other studies [44].…”
Section: Discussionsupporting
confidence: 87%
“…Studies on the effect of WD on starch are scanty: Sun-Ok and Dong-Hoon [43] found that WD concentrations of up to 0.5% decreased the leaf starch content of the orchid Neofinetia falcata but increased its root content. We have not assayed the root parts of the plant, but the starch content of our control lettuce leaves was consistent with that reported in other studies [44].…”
Section: Discussionsupporting
confidence: 87%
“…Incidentally, the abundance of the antiprotozoal microbe Oscillatoria nigro-viridis increased between brassica densities of 24 and 48 plants 39 . It was previously found that intraspecific competition in B. juncea manifested as increased counts of stress induced inflorescences and bolting 40 , 41 . In the present study, brassica bolted at the 24 and 48 plant densities which could be attributed to increasing intraspecific competition.…”
Section: Discussionmentioning
confidence: 98%
“…The starch and sucrose metabolism pathway plays a pivotal role in plant abiotic stress responses, including salt [34,35], drought [36], high temperature [37], and cold [38][39][40]. This pathway contributes to the accumulation of soluble sugars, thereby increasing cellular permeation concentration and water potential, and ultimately enhancing stress tolerance.…”
Section: Discussionmentioning
confidence: 99%